Rosmarius officinalis and propolis extract: Antioxidant properties and Echicoccus granulosus sensu lato protoscoleces inhibition activity - Dadeghi-Dehkordi, Z; Ghorbanipour, M; Sazmand, A; Daraei Garmakhany, A; Sari, A (Journal of the Hellenic Veterinary Medical Society, 2025)
Hydatidosis is an important zoonosis caused by the larval stage of several species of the genus Echinococcus. In humans, surgical removal of cysts is the treatment of choice, but leakage of cyst contents during surgery and formation of new cysts remains a concern. Currently, various solutions such as hypertonic saline and silver nitrate are used to inactivate the protoscolects living in the cysts. Therefore, the search for new protoscolicidal formulations with higher efficacy and lower side effects is always in focus. The aim of this study was to optimize the extraction conditions of Rosmarius officinalis and propolis extracts and to evaluate their antioxidant properties and lethal effects on protoscoleces of Echicoccus granulosus sensu lato in vitro. For this purpose, sheep livers with hydatid cysts were collected from a local slaughterhouse between September and December 2021. In the laboratory, the cysts were excised and the fertility and viability of protoscoleces were evaluated. Extracts of R. officinalis and propolis were prepared using different ethanol concentrations (0, 50, and 100% v/v) and different extraction times (24, 48, and 72 hours). Response Surface Methodology (RSM) was performed to determine the optimal extraction conditions. Finally, different concentrations of the optimized extracts (200, 400 and 600 ppm) were prepared and added to protoscoleces to study their protoscolicidal activity. The results showed that 100 µl/mL of the extract of R. officinalis prepared in 66.6 min with 77.01% ethanol inactivated 86.66, 100 and 100% of protoscoleces after 5, 15 and 30 min of exposure, respectively. Similarly, 100 µL/mL of the propolis extract prepared under optimal extraction conditions (67.79 minutes with ethanol 43.58 v/v) killed 94.16, 100, and 100% of the protoscoleces after 5, 15, and 30 minutes of exposure, respectively. The results of this in vitro study indicate that both organic materials can potentially be used in vivo.